Austenitic stainless steel flux-cored welding wire based on concentrated nitric acid corrosion resistance and preparation method
By developing a flux-core welding wire based on corrosion-resistant austenitic stainless steel, using specific chemical composition and preparation technology, the problem of poor corrosion resistance of existing welding materials in concentrated nitric acid environment is solved, and the corrosion resistance and welding performance of the welding wire are significantly improved.
Patent Information
- Application Number
- CN202411111735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The existing austenitic stainless steel welding materials have poor corrosion resistance in concentrated nitric acid environments, which are prone to intergranular corrosion and stress corrosion cracking, affecting the service life and safety of the equipment.
A corrosion-resistant austenitic stainless steel flux-core welding wire was developed based on corrosion resistance of concentrated nitric acid. By mixing chromium powder, nickel powder, coated modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder evenly, corrosion-resistant powder was obtained, and it was filled into the stainless steel strip, and the welding wire was made by a reduction machine to reduce the diameter.
It significantly improves the corrosion resistance and welding performance of welding wire in concentrated nitric acid environment, meets the use requirements in high corrosion environment, and makes the welded joints have high strength and toughness.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding materials for austenitic stainless steel, and in particular to a flux-cored welding wire for austenitic stainless steel resistant to concentrated nitric acid corrosion and a preparation method thereof. Background Art
[0002] In the fields of chemical industry, petroleum, aerospace, etc., materials resistant to concentrated nitric acid corrosion are often needed. Austenitic stainless steel is widely used in the manufacture of equipment and components resistant to concentrated nitric acid corrosion due to its good corrosion resistance and mechanical properties. However, in actual use, austenitic stainless steel needs to be welded. During the welding process, choosing a suitable welding wire is crucial to ensure the corrosion resistance and mechanical properties of the weld. For austenitic stainless steel resistant to concentrated nitric acid corrosion, the welding wire not only needs to have a good match with the base material, but also needs to have excellent corrosion resistance and welding performance. Common austenitic stainless steel welding materials have poor resistance to concentrated nitric acid corrosion. In a concentrated nitric acid environment, intergranular corrosion and stress corrosion cracking are prone to occur, which affects the service life and safety of the equipment and limits its application in certain specific fields. Therefore, it is of great significance to develop a flux-cored welding wire and preparation method based on austenitic stainless steel resistant to concentrated nitric acid corrosion. Summary of the invention
[0003] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide an austenitic stainless steel flux-cored welding wire and a preparation method based on concentrated nitric acid corrosion resistance, which solves the problem that the existing austenitic stainless steel welding materials have poor concentrated nitric acid corrosion resistance and are prone to intergranular corrosion and stress corrosion cracking in a concentrated nitric acid environment, thereby affecting the service life and safety of the equipment.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A flux-cored welding wire based on austenitic stainless steel that is resistant to concentrated nitric acid corrosion, comprising a welding wire sheath and corrosion-resistant powder wrapped inside the welding wire sheath:
[0006] Wherein, the corrosion-resistant powder comprises the following components in parts by weight:
[0007] 22-26 parts of chromium powder, 20-24 parts of nickel powder, 4.6-9.2 parts of coated modified titanium dioxide, 0.55-0.85 parts of boron nitride, 0.1-0.3 parts of manganese powder, 0.1-0.3 parts of molybdenum powder, 0.05-0.15 parts of cobalt powder and 41.5-48.5 parts of iron powder.
[0008] As a further solution of the present invention: the coated modified titanium dioxide is prepared by the following steps:
[0009] Step a1: Tetrabutyl titanate, hydrofluoric acid and deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 20-25° C. and a stirring rate of 300-400 r / min for 15-20 min, and then the mixture is heated to 160-170° C. and the stirring reaction is continued for 15-20 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 80-85° C. for 4-5 h to obtain fluorine-doped modified titanium dioxide;
[0010] Step a2: adding fluorine-doped modified titanium dioxide, tungsten hexachloride, polyvinyl pyrrolidone and anhydrous ethanol to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, ultrasonically treating for 20-30 minutes at an ultrasonic frequency of 40-50kHz, then adding ethyl orthosilicate solution dropwise while stirring at a temperature of 25-30°C and a stirring rate of 300-400r / min, and controlling the dropping rate to be 1-2 drops / s. After the dropwise addition is completed, adjusting the pH to 8.5-9 with an ammonia solution, then heating to 40-45°C and continuing to stir the reaction for 4-5 hours. After the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed with distilled water 2-3 times, then placed in a vacuum drying oven, and dried at a temperature of 40-45°C for 3-4 hours to obtain a composite modified titanium dioxide;
[0011] Step a3: Add polytetrafluoroethylene and anhydrous ethanol to a three-necked flask equipped with a thermometer and a stirrer, perform ultrasonic treatment for 20-30 minutes at an ultrasonic frequency of 40-50kHz, then add the composite modified titanium dioxide and stir the reaction for 4-5 hours at a temperature of 45-50°C and a stirring rate of 300-400r / min. After the reaction, cool the reaction product to room temperature and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3 hours. Then place it in a high-temperature resistance furnace and calcine it in an air environment at a temperature of 580-600°C for 2-3 hours. Then cool it with the furnace to obtain coated modified titanium dioxide.
[0012] As a further solution of the present invention: the usage ratio of tetrabutyl titanate, hydrofluoric acid and deionized water in step a1 is 20-25 mL: 5-7 mL: 80 mL.
[0013] As a further solution of the present invention: the mass fraction of the hydrofluoric acid in step a1 is 40%.
[0014] As a further solution of the present invention: the usage ratio of the fluorine-doped modified titanium dioxide, tungsten hexachloride, polyvinyl pyrrolidone, anhydrous ethanol and tetraethyl orthosilicate solution in step a2 is 10 mmol: 1-5 mmol: 0.2-0.4 g: 50-60 mL: 20-25 mL.
[0015] As a further solution of the present invention: the tetraethyl orthosilicate solution in step a2 is a solution formed by dissolving tetraethyl orthosilicate in anhydrous ethanol at a ratio of 8-10 mmol:10 mL.
[0016] As a further solution of the present invention: the mass fraction of the ammonia solution in step a2 is 25-27%.
[0017] As a further solution of the present invention: the usage ratio of the polytetrafluoroethylene, anhydrous ethanol and composite modified titanium dioxide in step a3 is 3-5g:50-55mL:15g.
[0018] As a further solution of the present invention: a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion comprises the following steps:
[0019] Step 1: Weigh 22-26 parts of chromium powder, 20-24 parts of nickel powder, 4.6-9.2 parts of coated modified titanium dioxide, 0.55-0.85 parts of boron nitride, 0.1-0.3 parts of manganese powder, 0.1-0.3 parts of molybdenum powder, 0.05-0.15 parts of cobalt powder and 41.5-48.5 parts of iron powder according to weight parts, and set aside;
[0020] Step 2: Mix chromium powder, nickel powder, coated modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder evenly, place in a vacuum drying oven, and dry at a temperature of 150-160° C. for 2-3 hours to obtain corrosion-resistant powder;
[0021] Step 3: Roll the 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shaped piece wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel cored welding wire based on concentrated nitric acid corrosion resistance.
[0022] Beneficial effects of the present invention:
[0023] The invention discloses an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion and a preparation method thereof. The invention comprises the following steps: uniformly mixing chromium powder, nickel powder, coated modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder and drying the mixture to obtain corrosion-resistant powder; rolling a stainless steel strip into a U-shape, filling the powder with the corrosion-resistant powder through a powder feeder, and then forming an O-shape with the corrosion-resistant powder wrapped therein; and then reducing the diameter of the austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion by using a reducing and drawing machine; the austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion significantly improves the corrosion resistance and welding performance of the welding wire in a concentrated nitric acid environment by optimizing the chemical composition and the preparation process, can meet the use requirements in a highly corrosive environment, and enables the welding joint to have higher strength and toughness, and can meet the performance requirements of the engineering structure for the welding joint; the austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion is suitable for welding of equipment, pipelines and structures in contact with concentrated nitric acid in industries such as chemical, petrochemical and pharmaceutical industries, and has broad application prospects.
[0024] In the process of preparing austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, a coated modified titanium dioxide was first prepared. First, tetrabutyl titanate was used as a raw material to prepare nano titanium dioxide. At the same time, hydrofluoric acid was added to the nano titanium dioxide to obtain fluorine-doped modified titanium dioxide. Then, nano silicon dioxide was prepared using tetraethyl orthosilicate, and tungsten hexachloride was added. A silicon dioxide layer doped with tungsten was coated on the surface of the fluorine-doped modified titanium dioxide to obtain a composite modified titanium dioxide. Finally, polytetrafluoroethylene was used as a coating precursor. The fluorine-containing substance generated by the high-temperature decomposition of ethylene fluoride reacts with the surface of the composite modified titanium dioxide, and a fluorine-containing layer is coated on the surface of the composite modified titanium dioxide to obtain a coated modified titanium dioxide; the small size effect and surface effect of the coated modified titanium dioxide make it have a higher specific surface area and surface activity, and can form more interface bonding points with the welding wire matrix, thereby improving the overall performance of the material and giving it excellent mechanical properties. The fluorine element has extremely strong electronegativity and chemical stability, and can be tightly wrapped on the surface of silicon dioxide to form a layer of The fluoride layer can not only effectively block the erosion of the corrosive medium, but also form a stable chemical bond with titanium dioxide to improve the overall stability of the composite material. Tungsten, as a metal element with a high melting point and high hardness, can be doped into titanium dioxide to change its crystal structure and introduce more defects and active sites. These defects and active sites help to adsorb and fix harmful ions in the corrosive medium, thereby slowing down the corrosion rate. At the same time, the addition of tungsten can also improve the thermal stability and mechanical strength of titanium dioxide. Therefore, there is a synergistic effect between the encapsulation of fluorine, the doping of tungsten and the nano effect. The protective effect of fluorine provides the first line of defense for the welding wire, and the doping effect of tungsten further enhances the corrosion resistance and mechanical properties of the material, while the nano effect makes this enhancement more significant and lasting. This synergistic effect together constitutes the excellent comprehensive performance of austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, which helps to form a uniform and dense weld joint, reduce welding defects, and improve the strength and sealing of the weld joint. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1:
[0027] This embodiment is a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, comprising the following steps:
[0028] Step S1: 20 mL of tetrabutyl titanate, 5 mL of hydrofluoric acid with a mass fraction of 40% and 80 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The reaction is stirred for 15 minutes at a temperature of 20° C. and a stirring rate of 300 r / min, and then the temperature is raised to 160° C. and the stirring reaction is continued for 15 hours. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 80° C. for 4 hours to obtain fluorine-doped modified titanium dioxide;
[0029] Step S2: 10 mmol of fluorine-doped modified titanium dioxide, 1 mmol of tungsten hexachloride, 0.2 g of polyvinyl pyrrolidone and 50 mL of anhydrous ethanol are added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and ultrasonically treated for 20 min at an ultrasonic frequency of 40 kHz, and then added dropwise with stirring at a temperature of 25° C. and a stirring rate of 300 r / min. 20 mL of an ethyl orthosilicate solution formed by dissolving 8 mmol:10 mL of ethyl orthosilicate in anhydrous ethanol is added, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the pH is adjusted to 8.5 with a 25% ammonia aqueous solution, and then the temperature is raised to 40° C. and the stirring reaction is continued for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 40° C. for 3 h to obtain a composite modified titanium dioxide;
[0030] Step S3: 3 g of polytetrafluoroethylene and 50 mL of anhydrous ethanol are added to a three-necked flask equipped with a thermometer and a stirrer, and ultrasonically treated for 20 min at an ultrasonic frequency of 40 kHz, then 15 g of composite modified titanium dioxide is added and stirred for 4 h at a temperature of 45 ° C and a stirring rate of 300 r / min. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 60 ° C for 2 h, and then placed in a high-temperature resistance furnace and calcined for 2 h in an air environment at a temperature of 580 ° C, and then cooled with the furnace to obtain coated modified titanium dioxide;
[0031] Step S4: weigh 22 parts of chromium powder, 20 parts of nickel powder, 4.6 parts of coated modified titanium dioxide, 0.55 parts of boron nitride, 0.1 parts of manganese powder, 0.1 parts of molybdenum powder, 0.05 parts of cobalt powder and 41.5 parts of iron powder according to weight parts, and set aside;
[0032] Step S5: mixing chromium powder, nickel powder, coated modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder uniformly, placing the mixture in a vacuum drying oven, and drying the mixture at 150° C. for 2 h to obtain corrosion-resistant powder;
[0033] Step S6: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shape wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel cored welding wire based on concentrated nitric acid corrosion resistance.
[0034] Embodiment 2:
[0035] This embodiment is a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, comprising the following steps:
[0036] Step S1: 22 mL of tetrabutyl titanate, 6 mL of hydrofluoric acid with a mass fraction of 40%, and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 22° C. and a stirring rate of 350 r / min for 18 min, and then the mixture was heated to 165° C. and the stirring reaction was continued for 18 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 82° C. for 4.5 h to obtain fluorine-doped modified titanium dioxide;
[0037] Step S2: 10 mmol of fluorine-doped modified titanium dioxide, 3 mmol of tungsten hexachloride, 0.3 g of polyvinyl pyrrolidone and 55 mL of anhydrous ethanol are added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and ultrasonically treated for 25 min at an ultrasonic frequency of 45 kHz, and then 22 mL of an ethyl orthosilicate solution formed by dissolving 9 mmol:10 mL of ethyl orthosilicate in anhydrous ethanol is added dropwise while stirring at a temperature of 28° C. and a stirring rate of 350 r / min, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the pH is adjusted to 8.5 with a 26% ammonia aqueous solution, and then the temperature is raised to 42° C. and the stirring reaction is continued for 4.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 42° C. for 3.5 h to obtain a composite modified titanium dioxide;
[0038] Step S3: 4 g of polytetrafluoroethylene and 52 mL of anhydrous ethanol are added to a three-necked flask equipped with a thermometer and a stirrer, and ultrasonically treated for 25 min at an ultrasonic frequency of 45 kHz, then 15 g of composite modified titanium dioxide is added and stirred for reaction at a temperature of 48° C. and a stirring rate of 350 r / min for 4.5 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 62° C. for 2.5 h, and then placed in a high-temperature resistance furnace and calcined for 2.5 h in an air environment at a temperature of 590° C., and then cooled with the furnace to obtain coated modified titanium dioxide;
[0039] Step S4: weigh 24 parts of chromium powder, 22 parts of nickel powder, 6.9 parts of coated modified titanium dioxide, 0.7 parts of boron nitride, 0.2 parts of manganese powder, 0.2 parts of molybdenum powder, 0.1 parts of cobalt powder and 45 parts of iron powder according to weight parts, and set aside;
[0040] Step S5: mixing chromium powder, nickel powder, coated modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder uniformly, placing the mixture in a vacuum drying oven, and drying the mixture at 155° C. for 2.5 hours to obtain corrosion-resistant powder;
[0041] Step S6: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shape wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel cored welding wire based on concentrated nitric acid corrosion resistance.
[0042] Embodiment 3:
[0043] This embodiment is a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, comprising the following steps:
[0044] Step S1: 25 mL of tetrabutyl titanate, 7 mL of hydrofluoric acid with a mass fraction of 40%, and 80 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 25° C. and a stirring rate of 400 r / min for 20 minutes, and then the mixture is heated to 170° C. and stirred for 20 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 85° C. for 5 hours to obtain fluorine-doped modified titanium dioxide;
[0045] Step S2: 10 mmol of fluorine-doped modified titanium dioxide, 5 mmol of tungsten hexachloride, 0.4 g of polyvinyl pyrrolidone and 60 mL of anhydrous ethanol are added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and ultrasonically treated for 30 min at an ultrasonic frequency of 50 kHz, and then 25 mL of an ethyl orthosilicate solution formed by dissolving 10 mmol:10 mL of ethyl orthosilicate in anhydrous ethanol is added dropwise while stirring at a temperature of 30° C. and a stirring rate of 400 r / min, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the pH is adjusted to 9 with a 27% ammonia aqueous solution, and then the temperature is raised to 45° C. and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 45° C. for 4 h to obtain a composite modified titanium dioxide;
[0046] Step S3: 5 g of polytetrafluoroethylene and 55 mL of anhydrous ethanol are added to a three-necked flask equipped with a thermometer and a stirrer, and ultrasonically treated for 30 min at an ultrasonic frequency of 50 kHz, then 15 g of composite modified titanium dioxide is added and stirred for 5 h at a temperature of 50° C. and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h, and then placed in a high-temperature resistance furnace and calcined at a temperature of 600° C. for 3 h in an air environment, and then cooled with the furnace to obtain coated modified titanium dioxide;
[0047] Step S4: weigh 26 parts of chromium powder, 24 parts of nickel powder, 9.2 parts of coated modified titanium dioxide, 0.85 parts of boron nitride, 0.3 parts of manganese powder, 0.3 parts of molybdenum powder, 0.15 parts of cobalt powder and 48.5 parts of iron powder according to weight parts, and set aside;
[0048] Step S5: mixing chromium powder, nickel powder, coated modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder uniformly, placing the mixture in a vacuum drying oven, and drying the mixture at 160° C. for 3 h to obtain corrosion-resistant powder;
[0049] Step S6: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shape wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel cored welding wire based on concentrated nitric acid corrosion resistance.
[0050] Comparative Example 1:
[0051] This comparative example is a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, comprising the following steps:
[0052] Step S1: weigh 26 parts of chromium powder, 24 parts of nickel powder, 0.85 parts of boron nitride, 0.3 parts of manganese powder, 0.3 parts of molybdenum powder, 0.15 parts of cobalt powder and 48.5 parts of iron powder according to weight parts, and set aside;
[0053] Step S2: mixing chromium powder, nickel powder, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder uniformly, placing the mixture in a vacuum drying oven, and drying the mixture at 160° C. for 3 h to obtain corrosion-resistant powder;
[0054] Step S3: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shaped strip wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel flux-cored welding wire based on concentrated nitric acid corrosion resistance.
[0055] Comparative Example 2:
[0056] This comparative example is a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, comprising the following steps:
[0057] Step S1: weigh 26 parts of chromium powder, 24 parts of nickel powder, 9.2 parts of nano titanium dioxide, 0.85 parts of boron nitride, 0.3 parts of manganese powder, 0.3 parts of molybdenum powder, 0.15 parts of cobalt powder and 48.5 parts of iron powder according to weight parts, and set aside;
[0058] Step S2: mixing chromium powder, nickel powder, nano titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder evenly, placing the mixture in a vacuum drying oven, and drying the mixture at 160° C. for 3 h to obtain corrosion-resistant powder;
[0059] Step S3: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shaped strip wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel flux-cored welding wire based on concentrated nitric acid corrosion resistance.
[0060] Comparative Example 3:
[0061] This comparative example is a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, comprising the following steps:
[0062] Step S1: 25 mL of tetrabutyl titanate, 7 mL of hydrofluoric acid with a mass fraction of 40%, and 80 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 25° C. and a stirring rate of 400 r / min for 20 minutes, and then the mixture is heated to 170° C. and stirred for 20 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 85° C. for 5 hours to obtain fluorine-doped modified titanium dioxide;
[0063] Step S2: weigh 26 parts of chromium powder, 24 parts of nickel powder, 9.2 parts of fluorine-doped modified titanium dioxide, 0.85 parts of boron nitride, 0.3 parts of manganese powder, 0.3 parts of molybdenum powder, 0.15 parts of cobalt powder and 48.5 parts of iron powder according to weight parts, and set aside;
[0064] Step S3: mixing chromium powder, nickel powder, fluorine-doped modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder uniformly, placing the mixture in a vacuum drying oven, and drying the mixture at 160° C. for 3 h to obtain corrosion-resistant powder;
[0065] Step S4: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shaped strip wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel flux-cored welding wire based on concentrated nitric acid corrosion resistance.
[0066] Comparative Example 4:
[0067] This comparative example is a method for preparing an austenitic stainless steel flux-cored welding wire resistant to concentrated nitric acid corrosion, comprising the following steps:
[0068] Step S1: 25 mL of tetrabutyl titanate, 7 mL of hydrofluoric acid with a mass fraction of 40%, and 80 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 25° C. and a stirring rate of 400 r / min for 20 minutes, and then the mixture is heated to 170° C. and stirred for 20 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 85° C. for 5 hours to obtain fluorine-doped modified titanium dioxide;
[0069] Step S2: 10 mmol of fluorine-doped modified titanium dioxide, 5 mmol of tungsten hexachloride, 0.4 g of polyvinyl pyrrolidone and 60 mL of anhydrous ethanol are added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and ultrasonically treated for 30 min at an ultrasonic frequency of 50 kHz, and then 25 mL of an ethyl orthosilicate solution formed by dissolving 10 mmol:10 mL of ethyl orthosilicate in anhydrous ethanol is added dropwise while stirring at a temperature of 30° C. and a stirring rate of 400 r / min, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the pH is adjusted to 9 with a 27% ammonia aqueous solution, and then the temperature is raised to 45° C. and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 45° C. for 4 h to obtain a composite modified titanium dioxide;
[0070] Step S3: weigh 26 parts of chromium powder, 24 parts of nickel powder, 9.2 parts of composite modified titanium dioxide, 0.85 parts of boron nitride, 0.3 parts of manganese powder, 0.3 parts of molybdenum powder, 0.15 parts of cobalt powder and 48.5 parts of iron powder according to weight parts, and set aside;
[0071] Step S4: mixing chromium powder, nickel powder, composite modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder uniformly, placing the mixture in a vacuum drying oven, and drying the mixture at 160° C. for 3 h to obtain corrosion-resistant powder;
[0072] Step S5: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shaped strip wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to reduce the diameter to Φ2.50 mm step by step to obtain an austenitic stainless steel flux-cored welding wire based on concentrated nitric acid corrosion resistance.
[0073] The flux-cored welding wires of austenitic stainless steel based on concentrated nitric acid corrosion resistance of Examples 1-3 and Comparative Examples 1-4 were subjected to surfacing welding experiments using C4 steel plate as the base material. The welding parameters were: welding current 190A, arc voltage 28V, welding speed 10m / h, and nitrogen and argon mixed gas flow rate 1L / min. The performance of the deposited metal was then tested, and the test results are shown in the following table:
[0074]
[0075] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the addition of coated modified titanium dioxide has a significant effect on improving the nitric acid corrosion resistance and mechanical properties of the welding wire.
[0076] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0077] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A flux-cored welding wire based on austenitic stainless steel resistant to concentrated nitric acid corrosion, characterized in that: Including welding wire sheath and corrosion-resistant powder wrapped inside the welding wire sheath: Wherein, the corrosion-resistant powder comprises the following components in parts by weight: 22-26 parts of chromium powder, 20-24 parts of nickel powder, 4.6-9.2 parts of coated modified titanium dioxide, 0.55-0.85 parts of boron nitride, 0.1-0.3 parts of manganese powder, 0.1-0.3 parts of molybdenum powder, 0.05-0.15 parts of cobalt powder and 41.5-48.5 parts of iron powder; Wherein, the coated modified titanium dioxide is prepared by the following steps: Step a1: Tetrabutyl titanate, hydrofluoric acid and deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 20-25° C. and a stirring rate of 300-400 r / min for 15-20 min, and then the mixture is heated to 160-170° C. and the stirring reaction is continued for 15-20 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 80-85° C. for 4-5 h to obtain fluorine-doped modified titanium dioxide; Step a2: adding fluorine-doped modified titanium dioxide, tungsten hexachloride, polyvinyl pyrrolidone and anhydrous ethanol to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, ultrasonically treating for 20-30 minutes at an ultrasonic frequency of 40-50kHz, then adding ethyl orthosilicate solution dropwise while stirring at a temperature of 25-30°C and a stirring rate of 300-400r / min, and controlling the dropping rate to be 1-2 drops / s. After the dropwise addition is completed, adjusting the pH to 8.5-9 with an ammonia solution, then heating to 40-45°C and continuing to stir the reaction for 4-5 hours. After the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed with distilled water 2-3 times, then placed in a vacuum drying oven, and dried at a temperature of 40-45°C for 3-4 hours to obtain a composite modified titanium dioxide; Step a3: Add polytetrafluoroethylene and anhydrous ethanol to a three-necked flask equipped with a thermometer and a stirrer, perform ultrasonic treatment for 20-30 minutes at an ultrasonic frequency of 40-50kHz, then add the composite modified titanium dioxide and stir the reaction for 4-5 hours at a temperature of 45-50°C and a stirring rate of 300-400r / min. After the reaction, cool the reaction product to room temperature and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3 hours. Then place it in a high-temperature resistance furnace and calcine it in an air environment at a temperature of 580-600°C for 2-3 hours. Then cool it with the furnace to obtain coated modified titanium dioxide.
2. The flux-cored welding wire based on austenitic stainless steel resistant to concentrated nitric acid corrosion according to claim 1, characterized in that: The usage ratio of tetrabutyl titanate, hydrofluoric acid and deionized water in step a1 is 20-25 mL: 5-7 mL: 80 mL.
3. The flux-cored welding wire based on austenitic stainless steel resistant to concentrated nitric acid corrosion according to claim 1, characterized in that: The mass fraction of the hydrofluoric acid in step a1 is 40%.
4. The flux-cored welding wire based on austenitic stainless steel resistant to concentrated nitric acid corrosion according to claim 1, characterized in that: The usage ratio of the fluorine-doped modified titanium dioxide, tungsten hexachloride, polyvinyl pyrrolidone, anhydrous ethanol and tetraethyl orthosilicate solution in step a2 is 10 mmol: 1-5 mmol: 0.2-0.4 g: 50-60 mL: 20-25 mL.
5. The flux-cored welding wire based on austenitic stainless steel resistant to concentrated nitric acid corrosion according to claim 1, characterized in that: The tetraethyl orthosilicate solution in step a2 is a solution formed by dissolving tetraethyl orthosilicate in anhydrous ethanol at a ratio of 8-10 mmol:10 mL.
6. The flux-cored welding wire based on austenitic stainless steel resistant to concentrated nitric acid corrosion according to claim 1, characterized in that: The mass fraction of the ammonia solution in step a2 is 25-27%.
7. The flux-cored welding wire based on austenitic stainless steel resistant to concentrated nitric acid corrosion according to claim 1, characterized in that: The usage ratio of the polytetrafluoroethylene, anhydrous ethanol and composite modified titanium dioxide in step a3 is 3-5g:50-55mL:15g.
8. A method for preparing austenitic stainless steel flux-cored welding wire based on concentrated nitric acid corrosion resistance according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Weigh 22-26 parts of chromium powder, 20-24 parts of nickel powder, 4.6-9.2 parts of coated modified titanium dioxide, 0.55-0.85 parts of boron nitride, 0.1-0.3 parts of manganese powder, 0.1-0.3 parts of molybdenum powder, 0.05-0.15 parts of cobalt powder and 41.5-48.5 parts of iron powder according to weight parts, and set aside; Step 2: Mix chromium powder, nickel powder, coated modified titanium dioxide, boron nitride, manganese powder, molybdenum powder, cobalt powder and iron powder evenly, place in a vacuum drying oven, and dry at a temperature of 150-160° C. for 2-3 hours to obtain corrosion-resistant powder; Step 3: Roll a 304 stainless steel strip with a width of 10 mm and a thickness of 0.3 mm into a U-shape, fill it with corrosion-resistant powder through a powder feeder with a filling rate of 40%, and then make it into an O-shape wrapped with corrosion-resistant powder. Then, use a reduction and drawing machine to gradually reduce the diameter to Φ2.50 mm to obtain an austenitic stainless steel cored welding wire based on concentrated nitric acid corrosion resistance.
Citation Information
Patent Citations
Flux-cored wire for welding austenitic stainless steel
CN102909490A